Philosophy in the crisis. Alejandro Korn and the educational reforms of Humanities - Fielbaum, Alejandro (Estudios de Filosofía, 2017)
In this work, we start by contextualizing Korn’s philosophy in the crisis of the Argentinian Centenary. Next, we will present his proposal for establishing an Argentinian philosophy capable of shaping the values that can guide national development, considered over and above pure economics. We show how Korn supports both discursively and institutionally the various projects for university reform, as he sees in them the possibility for constructing a new kind of university, capable of overcoming positivistic logic. In particular, his focus is on the School of Humanities due to its capability to establish a critical perspective, unyielding to mere instrumental logics.